A review of studies and modelling of solar radiation on human thermal comfort in outdoor environment. (15th April 2022) - Ji, Yuchen; Song, Jusheng; Shen, Pengyuan
Abstract: Thermal environment influences human thermal comfort significantly when people have outdoor activities. Four environmental parameters determine outdoor thermal comfort, which are air temperature, relative humidity, wind speed, and solar radiation. It is noteworthy that, different from the indoor environment, solar radiation significantly affects outdoor thermal comfort, which needs to be comprehensively understood and analyzed. In this paper, we focused on thermophysiological models and thermal comfort models with consideration of solar radiation, applications of these models, and discussed existing problems and future potential works. Here, those key points are summarized: (1) Many comprehensive thermophysiological models for simple and complex body models have been put forward. For solar load on the human body, Fanger's model showed a good fitting degree in predicting absorbed solar radiation. (2) Existing thermal indexes may not be suited to dynamic conditions of solar radiation while the DTS model may be a good example for thermal comfort evaluation under dynamic solar radiation. (3) For temporary conditions, non-Fourier models, such as the dual phase-lag model, may be applied in thermophysiological models due to the non-uniform internal structure of biological tissues. (4) A scheme of establishing dynamic thermal comfort models is put forward, considering dynamic features of environment parameters, thermophysiological parameters, and thermal adaptation. Highlights: Reviewing the effect of solar radiation in various thermophysiological models. Summarizing the effect of solar radiation on thermal comfort based on solar-corrected indexes. Reviewing the applications of thermophysiological models for individuals, urban development. Considering the dynamic thermal comfort models under non-steady solar radiation condition